Fitness Centers and Gyms from a Physical Education Perspective: A Literature Review on Their Concepts, Functions, and Contributions to Improving Public Health and Fitness - I Made Dwi Sastra Wargama; Amin Brilian Wicaksono Gussanto; Titis Pambudi; Wayan Kristin (Journal of Physical Education and Health Science, 2026)
This study addresses the growing paradox between the well-established benefits of physical activity and the persistent global prevalence of physical inactivity by examining the role of fitness centers and gyms from a physical education perspective. While these facilities are commonly viewed as spaces for exercise, their broader educational, behavioral, and public health contributions remain underexplored. Therefore, this study aims to analyze the concepts, functions, and contributions of fitness centers and gyms in promoting physical literacy and sustainable active lifestyles. A systematic literature review (SLR) was conducted following PRISMA 2020 guidelines, using data from Scopus, Web of Science, PubMed, and Google Scholar. A total of 245 records were identified, of which 20 studies met the inclusion criteria after screening and eligibility assessment. The findings indicate that fitness centers and gyms contribute significantly to improving physical fitness, metabolic health, and psychological well-being. Beyond physiological outcomes, these facilities also play an important role in shaping motivation, self-efficacy, and long-term engagement in physical activity. Additionally, factors such as accessibility, inclusivity, and socioecological influences were found to affect participation. The review further reveals that fitness environments can function as informal learning spaces that support the development of physical literacy, although this role remains underemphasized in existing research. In conclusion, fitness centers and gyms have substantial potential as strategic platforms for promoting public health and active lifestyles. A more integrative approach that combines physical, educational, and behavioral dimensions is needed to optimize their contribution within the broader context of physical education and public health.